ANALISIS DETERMINAN NILAI PERUSAHAAN INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA - Rizkyka Agsyana Amaretta, (2022)
This study aims to analyze and prove investment decisions through price earnings ratio (PER), funding decisions through debt to equity ratio (DER), and dividend policy through dividend payout ratio (DPR) towards firm value. This research used a quantitative approach. The sampling technique used was purposive sampling with 20 company in consumer goods industry. Data collection using a secondary data through annual report. The data analysis technique used descriptive and panel data analysis and processed by Eviews 10 software. The result of the study stated: (1) investment decisions has no effect towards firm value; (2) funding decisions has a negative effect towards firm value; and (3) dividend policy has no effect towards firm value.